The Vibration Analysis Of Kuih Loyang Mold Frame - Ismail, Ahmad Norarif Amin (Universiti Sains Malaysia, 2019)
Kuih Loyang is one of demand biscuits for most festival in Malaysia. The slow production of the biscuits has become as problem to meet the demand. The operator needs to work fast and effective to solve the problem of demand production. In addition, the heavy mold frame give some difficulty to operator to shake the biscuits fall off from the mold. In order to identify suitable motion to shake all the biscuits fall off from frame, the vibration motion of the mold frame was analyzed. The natural frequency and mode shape of the vibration motion should be known. By using modal analysis simulation and fixed support boundary conditions, the first 10 inherent natural frequencies and mode shapes of the vibration motion are evaluated. The natural frequencies are ranging from 165.97 Hz to 740.06 Hz. The mode shapes consists of lateral-torsional and axial bending vibration. Then, by experiment modal testing, the first 10 inheret natural frequencies and mode shapes of vibration motion are evaluated and compared with simulation.The experiment produced the highest amplitude, 0.64 g/N at natural frequency, 244.4 Hz. The percentage differences between both result according to highest amplitude for mode shapes number 3 is 5.07%. The comparing result for both analysis and testing shows a good agreement and its verified